Investigation of student engagement model of science teaching with ICT - Syed Hassan, Sharifah Sariah; Nik Abdul Rahman, Nik Suryani (EuroJournals Publishing, Inc., 2010)
This study was designed to validate the model of science teachers’ support of psychologicalbasic needs on student engagement. In the model, we also examined the relationships of each support namely autonomy, competence and relatedness based on the framework of Basic Psychological needs theory by Deci and Ryan (1985) and Skinner and Belmont (1993). The samples were taken from the population of Form 1, 2 and 4 from four secondary schools in the state of Selangor, Malaysia. Using AMOS (7.0), the Structural Equation Modeling (SEM) was conducted to investigate the overall model fit and significant relationships. The empirical results indicate that the hypothesized model was not fit. The model was then re-specified and the results show that only one predictor namely competence support will promote student engagement in learning. Relatedness support predicts engagement only through competence support. On the other hand,autonomy and relatedness are correlated. These relationships are explained and discussed further. Implications of the results are also addressed.